Evaluating an emerging technology-based biorefinery for edible house crickets - Psarianos, Marios; Ojha, Shikha; Schlüter, Oliver K. (Frontiers in Nutrition, 2023)
Edible insects and specifically house crickets are expected to play an important role in the future food systems due to their rich nutritional profile, low environmental impact and growing consumer acceptance as food. Their content in proteins, lipids, chitin and phenolics offer high potential for the valorization of their biomass into nutritional end products and fractions. Further, emerging food processing technologies and green solvents are relevant for improving the valorization process. Therefore, high pressure (HP) and ultrasound (US) processing were implemented in an insect biorefinery system, where a hexane/methanol/water solvent was used to separate fat, phenolics and a solid fraction containing proteins and chitin. Afterwards, a deep eutectic solvent of betaine and urea (B/U) was used to for protein and chitin isolation. A maximum of 15% of fat was isolated, without any positive effect from the US or HP treatments. US treatment enhanced the phenolic extraction yield by 38.69%, while HP negatively affected the antioxidant capacity. B/U was efficient in separating proteins and chitin and led to a protein concentrate with a protein content ≥80% and a chitinous fraction with a chitin content ≥70%. House cricket biomass can be refined into valuable fractions with a quick and simple method that makes the process industrially relevant.